1986
DOI: 10.1103/physrevlett.57.1181
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculation of the Residual Electrical Resistivity of Random Alloys

Abstract: Results of numerical calculations of the electrical resistivity of the following primary solidsolution alloys are presented: Cu(Zn), Cu(Ga), Cu(Ge), Ag(Pd), and Ni(Mo). Our theoretical model is one reported earlier by Butler and uses a charge-self-consistent Korringa-Kohn-Rostoker coherent-potential approximation. The calculations are valid for strong as well as weak scattering, and for the first time, vertex corrections are included. Excellent agreement is obtained with experiment for the resistivity. PACS nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 17 publications
4
29
0
Order By: Relevance
“…Below c = 0.3, the effect is negligible, whereas for larger concentrations, short-range order depresses the resistivity a little show- ing how the current is enhanced on a site when surrounded by unlike neighbors. Experimental measurements on Ag c Pd 1−c alloys find that annealing has a smaller effect 22,58 than in Cu c Zn 1−c in line with our calculations. It is also found that cold work causes little change to the resistivity suggesting that additional defects such as dislocations may already be present affecting the measurements.…”
Section: Effects Of Short-range Order On Resistivitysupporting
confidence: 90%
See 3 more Smart Citations
“…Below c = 0.3, the effect is negligible, whereas for larger concentrations, short-range order depresses the resistivity a little show- ing how the current is enhanced on a site when surrounded by unlike neighbors. Experimental measurements on Ag c Pd 1−c alloys find that annealing has a smaller effect 22,58 than in Cu c Zn 1−c in line with our calculations. It is also found that cold work causes little change to the resistivity suggesting that additional defects such as dislocations may already be present affecting the measurements.…”
Section: Effects Of Short-range Order On Resistivitysupporting
confidence: 90%
“…Omission of the effect of the latter can lead to an underestimate of the conductivity. 21,22 Although in principle the recently developed SCF-KKR-NLCPA method 38 can provide the appropriate self-consistent one-electron charge densities and potentials, ␥ C ͑r I ͒'s and v ␥ C ͑r I ͒, for our transport calculations, in these first applications, we use those generated by the faster, simpler SCF-KKR-CPA method 4,5 in order to explore the new aspects of our theory.…”
Section: Comparison To the Coherent Potential Approximation Cpa:mentioning
confidence: 99%
See 2 more Smart Citations
“…To study transport, however, a configuration-averaged product of Green's functions hGG * i is required, a more formidable undertaking. Worked out by Butler [183] and applied to binary alloys in a single site approximation, the multiple-scattering theory implementation [184] of transport theory in the CPA gave results in very good agreement with experiment and later on with supercell calculations [185]. The application to more complex systems, however, appeared daunting.…”
Section: Historymentioning
confidence: 99%